Peningkatkan Minat Belajar Siswa Sekolah Dasar materi Asmaulhusna menggunakan Pendekatan Technological Pedagogic Content Knowledge (TPACK) - Rio Afdira (Jurnal Indonesia Pendidikan Profesi Guru, 2024)
Learning will be more meaningful when what is learned makes a person have an interest in learning. This is where the task of a teacher is to apply the model and make the material presented as interesting as possible so that students have high interest and creativity in the learning process. The purpose of this study was to determine the implementation of the Technological Pedagogic Content Knowledge (TPACK) approach in increasing students' interest in learning asmaulhusna material in SDIT Nurul 'Ilmi Lubuk Pinang students. This type of research uses Classroom Action Research (CAR). This research was conducted in 2023. The research sample amounted to 20 students. Data collection using observation, interviews, and questionnaires (tests). Data analysis was carried out including data reduction, data display, and conclusion drawing/verification. The results of the study obtained the conclusion that the implementation of the TPACK approach can increase students' interest in learning asmaulhusna material in class IV Nurul 'Ilmi Lubuk Pinang Integrated Islamic Elementary School, an increase in student interest in learning can be seen from pre-action to cycle I and II by following 4 stages in PTK, namely, planning, action, observation, and reflection stages.